Opening The Door: Immigration and Integration of Holocaust Survivors in Vancouver, 1947-1970 - Gerber, Jean (Canadian Jewish Studies / Études juives canadiennes, 1997)
Holocaust survivors who came to Canada have been characterized as alienated from Canadian Jewish life. Often, however, no objective study has been conducted of how survivors interacted with the economic, social and cultural life of their host communities in order to substantiate this claim. This paper studies survivors’ residential and occupational patterns after coming to Vancouver, and examines their affiliations with community organizations. It combines objective data with oral interviews to demonstrate how survivors integrated into the Vancouver host Jewish community and whether or not they remained alienated from it.